2005
DOI: 10.1021/es0500355
|View full text |Cite
|
Sign up to set email alerts
|

N2O Emissions from Streams in the Neuse River Watershed, North Carolina

Abstract: We present N2O emission data from 11 sites in the Neuse River watershed. Emissions were measured using a static surface enclosure technique deployed on eight sites on the main river channel and three tributary sites. Ancillary data collected included dissolved oxygen, nitrate, total nitrogen, ammonium, dissolved organic carbon, total phosphorus, and temperature. Analysis using standard linear models, and classification and regression trees (CART), indicated nitrate to be the primary driving variable associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 18 publications
1
33
3
2
Order By: Relevance
“…This contrasts with past results from two river systems, where NO 3 − explained 52-68% of variation in N 2 O emissions over time [McMahon and Dennehy, 1999;Stow et al, 2005]. However, the poorer relationships we report are commonly observed, particularly in areas affected by groundwater N 2 O inputs [Clough et al, 2006].…”
Section: Spatial and Temporal Variation In Stream N 2 O Fluxescontrasting
confidence: 99%
See 1 more Smart Citation
“…This contrasts with past results from two river systems, where NO 3 − explained 52-68% of variation in N 2 O emissions over time [McMahon and Dennehy, 1999;Stow et al, 2005]. However, the poorer relationships we report are commonly observed, particularly in areas affected by groundwater N 2 O inputs [Clough et al, 2006].…”
Section: Spatial and Temporal Variation In Stream N 2 O Fluxescontrasting
confidence: 99%
“…Shorter-term or seasonal studies exist for a much broader range of streams and rivers systems. While our data set represents the longest-term study, others have focused more upon spatial gradients [Stow et al, 2005], or among-stream variation [Harrison and Matson, 2003;Beaulieu et al, 2008]. Emissions from our study streams were considerably lower than those observed from eutrophic subtropical streams Results of a simple regression analysis for all small streams for which there are published annual flux data are also presented.…”
Section: Annual N 2 O Fluxesmentioning
confidence: 95%
“…N 2 O emission rates were also calculated for comparison with the literature, but were nearly equivalent to in-stream production, ranging from -0.09 at MH to 202 lmol N m -2 h -1 at BC (or 74-100 % of total flux at BC). N 2 O emissions in the BC stream reaches were among the highest published values from lotic systems which have ranged up to 175 lmol N m -2 h -1 (Beaulieu et al 2007;Harrison et al 2005;Hemond and Duran 1989;Stow et al 2005), although higher episodic emissions (*4000 lmol N m -2 h -1 ) have been observed in extremely N polluted systems near wastewater treatment facilities (Hasegawa et al 2000).…”
Section: Gas Transfer Velocitymentioning
confidence: 86%
“…to evaluate gas emission fluxes and factors regulating CH 4 and N 2 O fluxes. These studies indicate that anthropogenic emissions of N 2 O represent around 30-45 % of the present-day global emissions and over 60 % of CH 4 emissions (Chen et al 2010a, b;Stadmark and Leonardson 2007;Stow et al 2005). Quantification of greenhouse gas (GHG) emissions from different natural landforms has become a priority research topic in China in efforts to generate emission inventories and develop strategies to reduce greenhouse gas emissions (Garg et al 2012).…”
Section: Introductionmentioning
confidence: 99%